2017
DOI: 10.3389/fimmu.2017.01701
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Receptor Deficiency Attenuates Neuroinflammation through the Induction of Apolipoprotein E

Abstract: ObjectiveWe aimed to determine the role of the low-density lipoprotein receptor (LDLr) in neuroinflammation by inducing experimental autoimmune encephalomyelitis (EAE) in ldlr knock out mice.MethodsMOG35–55 induced EAE in male and female ldlr−/− mice was assessed clinically and histopathologically. Expression of inflammatory mediators and apolipoprotein E (apoE) was investigated by qPCR. Changes in protein levels of apoE and tumor necrosis factor alpha (TNFα) were validated by western blot and ELISA, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
(42 reference statements)
0
18
1
Order By: Relevance
“…From our study, we found PAI-1 increased in WT mice exposed to PG with nicotine, but this increase was significantly reduced in KO mice, indicating that the SKIL-TGFβ-PAI-1 connection may be regulated by nAChR α7 when challenged with e-cig aerosol containing nicotine. In relation to the other significantly altered target, LDLR, previous publications have proved that it is related to inflammatory processes [40,41]. Ricci et al identified that LDLR is associated with macrophage differentiation [40]; and that LDLR deficiency is capable of reducing inflammatory responses in THP-1 cells [40], as well as inhibiting the pro-inflammatory cytokines in the central nervous system [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our study, we found PAI-1 increased in WT mice exposed to PG with nicotine, but this increase was significantly reduced in KO mice, indicating that the SKIL-TGFβ-PAI-1 connection may be regulated by nAChR α7 when challenged with e-cig aerosol containing nicotine. In relation to the other significantly altered target, LDLR, previous publications have proved that it is related to inflammatory processes [40,41]. Ricci et al identified that LDLR is associated with macrophage differentiation [40]; and that LDLR deficiency is capable of reducing inflammatory responses in THP-1 cells [40], as well as inhibiting the pro-inflammatory cytokines in the central nervous system [41].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the other significantly altered target, LDLR, previous publications have proved that it is related to inflammatory processes [40,41]. Ricci et al identified that LDLR is associated with macrophage differentiation [40]; and that LDLR deficiency is capable of reducing inflammatory responses in THP-1 cells [40], as well as inhibiting the pro-inflammatory cytokines in the central nervous system [41]. In our study, downregulation of LDLR was seen in PG with nicotine exposed WT mice while this effect was significantly reduced in mice with the nAChR α7 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous APOE and exogenous APOE mimetic peptides reduced glial activation and inflammatory cytokines release after CNS disease. Interestingly, blocking inflammatory signaling effectively increases APOE expression in neuroinflammatory processes (Pocivavsek and Rebeck, 2009 ; Mailleux et al, 2017 ). These evidences suggest that APOE production and inflammation are in a negative feedback loop, with APOE suppressing inflammation and inflammation suppressing APOE production.…”
Section: Discussionmentioning
confidence: 99%
“…LXR activation decreases disease severity, Th17 polarization and IL-17 secretion in EAE, though certain oxysterols may have pro-inflammatory effects in these models [ 64 ]. The Mailleux group also reported that in EAE, LDL receptor deficiency attenuates the severity of the disease in females (not in males) mice, through the induction of ApoE [ 65 ]. Interestingly, other authors have found that, in ApoE knock-out mice, ApoE deficiency increases EAE severity only in female animals [ 8 ].…”
Section: Genesis and Repair Of Ms Lesionsmentioning
confidence: 99%
“…RRMS subjects have smaller LDL in comparison to healthy controls and in some cases increased levels of small HDL with impaired anti-inflammatory activity [ 88 ]. Interestingly, this study observed some differences between male and female patients, suggesting gender differences in lipid metabolism associated with MS [ 65 ]. Supporting this hypothesis, recent research from our group suggests that sex steroids modify the serum lipid profile associated with disability in these patients (unpublished results).…”
Section: Systemic Metabolism In Msmentioning
confidence: 99%